2015
DOI: 10.1097/qco.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HIV drug resistance

Abstract: Sensitive resistance testing methods are mainly confined to research applications and in this context have provided great insight into the dynamics of drug resistance development, persistence, and transmission. Adoption in care settings is becoming increasingly possible, although important challenges remain. Platforms for diagnostic use must undergo technical improvements to ensure good performance and ease of use, and clinical validation is required to ensure utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Consensus sequences and frequencies of reads were produced as previously described; reads were analysed applying a 1% interpretative cut-off. 19 , 20 RAMs considered major in the resistance analysis are reported in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Consensus sequences and frequencies of reads were produced as previously described; reads were analysed applying a 1% interpretative cut-off. 19 , 20 RAMs considered major in the resistance analysis are reported in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of discussion in this paper, we reported a variant detection limit of >1% as resistant variants at this level have been shown to be clinically relevant [ 10 , 32 34 ]. In addition, the level of >1% was chosen as the 454 platform used in this study has demonstrated high intralaboratory and interlaboratory consistency in the detection of mutants present at a frequency between 1 and 10% in a large multicentre evaluations [ 35 37 ]…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that low-frequency variants with mutations affecting the NNRTIs, and to a lesser extent the NRTIs, significantly reduce responses to first-line therapy with two NRTIs plus one NNRTI, while showing no appreciable effect on bPI-based regimens. 17–20 However, transmission is unlikely to be a source of the large majority of these low-frequency variants in individuals who have recently acquired HIV and consequently would have minimal to no impact on treatment outcome as they would not have been selected under drug pressure. 21 …”
Section: Introductionmentioning
confidence: 99%